2022
DOI: 10.1186/s13148-022-01272-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study of bronchopulmonary dysplasia in preterm infants: results from the discovery-BPD program

Abstract: BackgroundBronchopulmonary dysplasia (BPD) is a lung disease in premature infants caused by therapeutic oxygen supplemental and characterized by impaired pulmonary development which persists into later life. While advances in neonatal care have improved survival rates of premature infants, cases of BPD have been increasing with limited therapeutic options for prevention and treatment. This study was designed to explore the relationship between gestational age (GA), birth weight, and estimated blood cell-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 97 publications
2
24
0
Order By: Relevance
“…In addition to the immunological biomarkers, we also observed development-and alveolarization-related epigenetic and transcriptomic markers in cord blood of infants who developed BPD 30,31,40 . Concurrently with BPD epigenome data 22 , we identified SPOCK2 and AGER among the BPD-DEGs in cord blood. SPOCK2, a BPD www.nature.com/scientificreports/ susceptibility gene identified from GWAS 7,30,31 , was reported to be deleterious in BPD development as its overexpression in the lung altered neonatal mouse lung alveolarization and exacerbated hyperoxia-caused alveolar simplification while anti-SPOCK2 antibody treatment in mice improved it 7,30 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition to the immunological biomarkers, we also observed development-and alveolarization-related epigenetic and transcriptomic markers in cord blood of infants who developed BPD 30,31,40 . Concurrently with BPD epigenome data 22 , we identified SPOCK2 and AGER among the BPD-DEGs in cord blood. SPOCK2, a BPD www.nature.com/scientificreports/ susceptibility gene identified from GWAS 7,30,31 , was reported to be deleterious in BPD development as its overexpression in the lung altered neonatal mouse lung alveolarization and exacerbated hyperoxia-caused alveolar simplification while anti-SPOCK2 antibody treatment in mice improved it 7,30 .…”
Section: Discussionmentioning
confidence: 85%
“…DNA methylation microarray analysis. Aliquots (100-500 ng) of genomic DNA from whole peripheral blood were bisulfite-converted using EZ-96 DNA Methylation MagPrep kits (Zymo Research, Irvine, CA) following the manufacturer's instructions as described previously 22 . Bisulfite-converted DNAs were applied to Human MethylationEPIC BeadChip (Illumina, San Diego, CA), which covers over 850,000 CpG sites in the human genome, at the NIEHS Molecular Genomics Core Laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an epigenome-wide association study found significant differences in the DNA methylation patterns in cord blood of preterm neonates who subsequently developed BPD compared with those who did not develop lung disease (Ref. 11).…”
Section: The Role Of Dna Methylation In Early Lifementioning
confidence: 99%
“…In this review, we will discuss DNA methylation, which has been linked to early development and neonatal disease (Refs 8, 9, 10, 11, 12, 13, 14, 15, 16). We will specifically focus on the intestinal disease of prematurity, necrotizing enterocolitis (NEC).…”
Section: Introductionmentioning
confidence: 99%